Natural or Human Landscape Beauty? Quantifying Aesthetic Experience at Longji Terraces Through Eye-Tracking - Ting Zhang; Yue Jiang; Donghong Liu; Shijie Zeng; Pengjin Sheng (Journal of Eye Movement Research, 2025)
This study investigated tourists’ visual perception, aesthetic experience, and behavioral intentions across four types of landscapes. A total of 353 questionnaires were distributed on-site, and the SOR model was used to examine the visual stimuli and aesthetic responses perceived by tourists, followed by laboratory eye-tracking to observe tourists’ points of attention on the Longji Terraced Fields landscape Key findings reveal that different residences and revisiting conditions affect tourists’ visual attention, with the most attention given at the intersections of landscape elements. Furthermore, although landscape visual stimuli do not significantly affect the intention response, eye movement parameters are positively correlated with aesthetic experience. The study contributes to understanding tourist aesthetic perception in terraced rice field landscapes and provides Chinese cases for the aesthetic appreciation of the terrace landscape.